2014
DOI: 10.1186/s12913-014-0543-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the internal construct validity of the Personal Care Participation Assessment and Resource Tool (PC-PART) using Rasch analysis

Abstract: BackgroundThe Personal Care Participation Assessment and Resource Tool (PC-PART) is a 43-item, clinician-administered assessment, designed to identify patients’ unmet needs (participation restrictions) in activities of daily living (ADL) required for community life. This information is important for identifying problems that need addressing to enable, for example, discharge from inpatient settings to community living. The objective of this study was to evaluate internal construct validity of the PC-PART using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This occurs where the response to one item is not dependent on the response to another item [ 18 , 26 ]. Person-item residual correlation value <0.2 indicates local independence [ 34 ]. Internal consistency reliability The degree to which items in each scale measure the same construct [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This occurs where the response to one item is not dependent on the response to another item [ 18 , 26 ]. Person-item residual correlation value <0.2 indicates local independence [ 34 ]. Internal consistency reliability The degree to which items in each scale measure the same construct [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“… Internal consistency reliability The degree to which items in each scale measure the same construct [ 16 ]. Person Separation Index (PSI) > 0.7 indicates good internal consistency reliability [ 15 , 28 , 34 ]. Response format Whether or not participants are able to consistently choose a response category appropriate for their level of health literacy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each Not OK represented an ADL participation restriction. These item response categories were shown to be valid using Rasch analysis [ 32 ]. When used clinically, the raw score for each scale is the total number of Not OK scores observed for an individual patient, with a range of possible scores of 0–16 ( Self Care ) and 0–14 ( Domestic Life ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent research has demonstrated that the PC-PART has good inter-rater reliability for group applications but not for individual applications, such as in the clinical setting [ 31 ]. Using Rasch methods, a further study generated evidence supporting internal validity of 30 of the original 43 items, when grouped into separate Self Care (16 items) and Domestic Life (14 items) scales [ 32 ]. The objective of this present study was to evaluate the construct validity, criterion validity and responsiveness of the Rasch-derived Self Care and Domestic Life scales in an adult inpatient rehabilitation setting.…”
Section: Introductionmentioning
confidence: 99%